2015
DOI: 10.1002/2015gl065378
|View full text |Cite
|
Sign up to set email alerts
|

Upper ocean response to Hurricane Gonzalo (2014): Salinity effects revealed by targeted and sustained underwater glider observations

Abstract: During October 2014, Hurricane Gonzalo traveled within 85 km from the location of an underwater glider situated north of Puerto Rico. Observations collected before, during, and after the passage of this hurricane were analyzed to improve our understanding of the upper ocean response to hurricane winds. The main finding in this study is that salinity potentially played an important role on changes observed in the upper ocean; a near‐surface barrier layer likely suppressed the hurricane‐induced upper ocean cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 25 publications
(46 reference statements)
4
68
0
Order By: Relevance
“…However, the issue is controversial. Some studies suggest that the BL is favorable for TC intensification [e.g., Wang et al ., ; Neetu et al ., ; Balaguru et al ., ; Vissa et al ., ; Domingues et al ., ]; but some recent studies, on the other hand, demonstrate that the BL has little impact on TC intensification [ Newinger and Toumi , ; Hernandez et al ., 2016]. Here we show that the influence of the BL on TCs is complex dependent on the stages and processes such as TC intensity and ocean stratification associated with the BL.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, the issue is controversial. Some studies suggest that the BL is favorable for TC intensification [e.g., Wang et al ., ; Neetu et al ., ; Balaguru et al ., ; Vissa et al ., ; Domingues et al ., ]; but some recent studies, on the other hand, demonstrate that the BL has little impact on TC intensification [ Newinger and Toumi , ; Hernandez et al ., 2016]. Here we show that the influence of the BL on TCs is complex dependent on the stages and processes such as TC intensity and ocean stratification associated with the BL.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As Gonzalo passed near the glider, it intensified from a Category-2 to a Category-3 hurricane (Figure 6a). Glider observations indicated that hurricaneinduced SST cooling forced by Gonzalo was largely suppressed by the presence of a low-salinity layer in the upper 20 m of the ocean (i.e., a barrier layer; Domingues et al, 2015). The presence of this barrier layer may have favored the storm's intensification, as Gonzalo continued intensifying into a Category-4 hurricane .…”
Section: Alps-enabled Improvements In Tc Ocean-induced Dynamics and Imentioning
confidence: 99%
“…In general, fields of TCHP show high spatial and temporal variability associated mainly with oceanic mesoscale features and interannual variability (e.g., ENSO), or long-term decadal variability. This variability can be identified using satellite altimetry and in situ observations (Goni et al 1996;Lin et al 2008;Pun et al 2013;Domingues et al 2015), similar to analyses of meridional heat transport in the Atlantic Ocean (Dong et al 2015).…”
Section: G Tropical Cyclone Heat Potential-g J Goni J a Knaff mentioning
confidence: 99%